COMPARISON OF MORPHOLOGICAL CHARACTERISTICS AND FUNCTIONAL PROPERTIES OF THE UDDER IN COWS - Ліщук, С. Г. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
As a result of studies it has been found breed features of morphological characteristics and functional properties of the udder in cows of Ukrainian black-and-white and red-and-white Ukrainian dairy breeds. Udder measurements of cows of Ukrainian black and white dairy cattle exceedmeasurements of cows of Ukrainian red-spotted milk breed. Udder index is 1.2% higher in cows of Ukrainian black and white dairy cattle. Difference between breeds on this indicator such as time of milking was higher at 2.1 minutes in cows of Ukrainian black and white dairy cattle. Animals of Ukrainian black and white dairy cattle also dominated by setting a daily yield of 11.6 kg.